2019
DOI: 10.1002/rcr2.426
|View full text |Cite
|
Sign up to set email alerts
|

Severe mediastinitis over a month after endobronchial ultrasound‐guided transbronchial needle aspiration

Abstract: Although endobronchial ultrasound‐guided transbronchial needle aspiration (EBUS‐TBNA) has been reported to be a minimally invasive and relatively safe procedure, mediastinitis is a serious complication related to the procedure. The median time of mediastinitis onset is approximately 12 days after EBUS‐TBNA. Here we report two rare cases with mediastinitis onset 40 and 53 days after EBUS‐TBNA. Surgical drainage was performed since systemic treatment with antibiotics was insufficient in both cases. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…In studies of endoscopic fine needle aspiration, cystic or necrotic lesions were associated with postoperative infectious complications 15 . However, as in our case, mediastinitis occurred in some cases, even when the lesions were noncystic and non‐necrotic 11 . The number of samples obtained by EBUS TBNA for each LN and unskilled operator can also be possible risk factors for mediastinitis 3 .…”
Section: Discussionmentioning
confidence: 51%
See 3 more Smart Citations
“…In studies of endoscopic fine needle aspiration, cystic or necrotic lesions were associated with postoperative infectious complications 15 . However, as in our case, mediastinitis occurred in some cases, even when the lesions were noncystic and non‐necrotic 11 . The number of samples obtained by EBUS TBNA for each LN and unskilled operator can also be possible risk factors for mediastinitis 3 .…”
Section: Discussionmentioning
confidence: 51%
“…Among these complications, infectious complications can be serious and require surgical treatment 3,7–9 . They are associated with a longer duration of hospitalization and delayed initiation of subsequent anticancer treatment after diagnosis 10,11 . Infectious complications after EBUS TBNA are rare; a systematic review and a national survey previously reported the rate of infectious complications was 0.02%–0.19% 4,12,13 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[ 11 ] The use of EBUS-TBNA has related complications such as secondary infection and hemorrhage, especially for cystic lesions, which seems to have a greater potential to develop cystic infection, lung abscess, pleural infection or mediastinal infection than solid lesions of the mediastinum. [ 4 , 6 , 9 , 13 , 16 , 25 ] The reported infectious pathogens include Streptococcus, [ 5 6 , 16 17 , 24 25 , 30 31 ] Coryneform bacteria and Prevotella melaninogenica, [ 5 ] Staphylococcus, [ 4 , 24 ] Mycobacterium tuberculosis, [ 21 ] Haemophilus Influenza, [ 32 ] Eikenella corrodens, [ 24 , 33 ] Klebsiella pneumonia, Actinomyces odontolyticus, Gemella morbillorum, Prevotella buccae, Actinomyces, [ 30 ] among which the most of the reported bacteria are oral flora. During the procedure of EBUS-BNA, the bronchoscope and needle may be contaminated when passing through the oropharynx, thus carrying bacteria of the oral flora into the cyst.…”
Section: Discussionmentioning
confidence: 99%